2016
DOI: 10.7759/cureus.775
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Evaluation of Zero-Profile Devices Compared to Stand-Alone PEEK Cages for the Treatment of Three- and Four-Level Cervical Disc Disease

Abstract: Background: Anterior cervical discectomy and fusion (ACDF) is a well-accepted treatment option for patients with cervical spine disease. Three- and four-level discectomies are known to be associated with a higher complication rate and lower fusion rate than single-level surgery. This study was performed to evaluate and compare zero-profile fixation and stand-alone PEEK cages for three- and four-level ACDF.Methods: Two cohorts of patients who underwent ACDF for the treatment of three- and four-level disease wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 31 publications
0
17
0
1
Order By: Relevance
“…However, in most cases and in most of the studies, this remains asymptomatic. Gerszten et al [1] evaluated the results of multi-level ACDF using stand-alone cages and zero-profile instrumentation and concluded that both techniques are safe and effective, comparable with the reports that used plates [25]. The safety of stand-alone cages has been studied in a large cohort of patients as discussed in the literature [9].…”
Section: Radiological Outcomesmentioning
confidence: 96%
See 2 more Smart Citations
“…However, in most cases and in most of the studies, this remains asymptomatic. Gerszten et al [1] evaluated the results of multi-level ACDF using stand-alone cages and zero-profile instrumentation and concluded that both techniques are safe and effective, comparable with the reports that used plates [25]. The safety of stand-alone cages has been studied in a large cohort of patients as discussed in the literature [9].…”
Section: Radiological Outcomesmentioning
confidence: 96%
“…Multi-level disc disease of the cervical spine represents a challenging problem. Although a variety of anterior, posterior, and combined approaches have been advocated for multi-level cervical disc disease, the anterior approach still represents the preferable surgery in many cases as it allows for the direct decompression of the spinal cord and nerve roots as well as achieving solid fusion [ 1 ]. Multi-level cervical discectomy is often combined with anterior or posterior instrumentation to maintain the spinal curvature and increase the fusion rate [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After reviewing 10 studies consisting of over 700 patients in their meta-analysis, Dong et al concluded that zero-profile spacers conferred similar fusion rates, lower Neck Disability Index (NDI), and improved pain scores compared to standard anterior plating [ 28 ]. These favorable outcomes were replicated in both single level and multi-level cervical disc diseases, suggesting the safety of zero-profile spacers regardless of number of cervical levels involved [ 40 , 41 ].…”
Section: Reviewmentioning
confidence: 99%
“…35,40,49,57 Of note, stand-alone devices were found to be an effective treatment option for patients with up to 3-and 4-level spine disease as well. 57,58 However, one potential disadvantage of the standalone technique is an increased incidence of subsidence in the stand-alone device fusions when compared with traditional ACDF that is described in literature. [59][60][61] In this meta-analysis, NDI, VAS arm, VAS neck, and JOA scoring appeared the same between stand-alone ACDF and CDA, thus suggesting similar patient experience from the 2 treatments.…”
Section: Summary Of Evidencementioning
confidence: 99%